2017
DOI: 10.4067/s0718-07642017000100014
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de la Adición de Goma Gelana sobre las Propiedades de Barrera y Físico Mecánicas de Biopelículas Binarias

Abstract: * Autor a quien debe ser dirigida la correspondencia.Recibido Ago. 24, 2016; Aceptado Oct. 18, 2016; Versión final Nov. 21, 2016, Publicado Feb. 2017 Resumen El objetivo del presente estudio fue caracterizar las propiedades físico mecánicas y de barrera al vapor de agua de biopelículas (BP) a base de carboximetilcelulosa (CMC) y goma xantana (GX) formuladas con varias concentraciones de goma gelana de bajo acilo (GBA). Las BP fueron elaboradas por el método de casting y posteriormente fueron determinadas la pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…The permeability values were different from other types of films, this can be attributed to the source of the hydrocolloid, the thickness and the differences in the process of elaboration and analysis [21]. Gonzáles et al, [22] reported that water vapour permeability values of binary carboxymethyl cellulose and xanthan gum biofilms increased significantly as the addition of low-acillusgelatine gum increased. Such behaviour may be due to the influence of crosslinking reactions on the moisture diffusion coefficient within the polymer network, indicating structural changes in the polymer matrix.…”
Section: Permeability Of the Edible Filmmentioning
confidence: 97%
See 1 more Smart Citation
“…The permeability values were different from other types of films, this can be attributed to the source of the hydrocolloid, the thickness and the differences in the process of elaboration and analysis [21]. Gonzáles et al, [22] reported that water vapour permeability values of binary carboxymethyl cellulose and xanthan gum biofilms increased significantly as the addition of low-acillusgelatine gum increased. Such behaviour may be due to the influence of crosslinking reactions on the moisture diffusion coefficient within the polymer network, indicating structural changes in the polymer matrix.…”
Section: Permeability Of the Edible Filmmentioning
confidence: 97%
“…These changes may have been due to the formation of new functional groups (carboxyl and acetyl groups) in amylopectin during the modification, which caused hydrogen bonds in starch to strengthen, facilitating water penetration into the granules [25]. Gonzalez et al, [22] reported that the stress resistance (RT) of control biofilms showed lower RT values, increasing as low-acillusgelana concentrations were higher, possibly to increased crosslinking reactions. The higher RT values (25.02MPa) were obtained in the film with 0.7% low-acillus gel gum.…”
Section: Tensile Strengthmentioning
confidence: 99%